PENYALURAN ZAKAT FITRAH OLEH AMIL DI LUAR MUSTAHIQ DI MASJID AL-MANAR DESA TEMPAPAN KUALA - NIM. A1011211069, WAHIDAH (Jurnal Fatwa Hukum, 2025)
Abstract Zakat is a form of worship prescribed in Islam and obligatory for every able Muslim. Zakat has a very important function, namely helping those in need and realizing social justice in society. One type of zakat is zakat fitrah which must be paid every month of Ramadan and must be distributed to eight groups of mustahiq as regulated in the Qur'an, Surah At-Taubah, verse 60 and Law Number 23 of 2011 concerning Zakat Management. However, in practice, the distribution of zakat fitrah carried out by amil at the Al-Manar mosque in Tempapan Kuala village has not been in accordance with these provisions, because in addition to zakat fitrah being distributed to the poor, needy, amil, and converts, zakat fitrah is also distributed to parties such as village shamans, midwives, gravediggers, Quran teachers, muezzins, ma'asyiral, preachers, and mosque imams. The research problem is formulated as follows: "What factors cause the distribution of zakat fitrah by amils outside the mustahiq (recipients) at the Al-Manar Mosque in Tempapan Kuala Village?" The purpose of this study is to determine the factors that cause the distribution of zakat fitrah outside the mustahiq, the legal consequences, and the efforts that can be made to ensure that zakat fitrah distribution complies with Islamic law. This research is an empirical juridical legal study with a qualitative descriptive approach. The data used were obtained through field research and library research. The data collection techniques used by the author were: first, direct communication (interviews) with data sources, namely the zakat committee and religious leaders of the Al-Manar Mosque in Tempapan Kuala Village. Second, indirect communication (questionnaires) with the community receiving zakat fitrah outside the mustahiq at the Al-Manar Mosque in Tempapan Kuala Village. The study population included religious leaders, the zakat collection committee, and recipients of zakat fitrah outside the mustahiq (receiver recipients) at the Al-Manar Mosque in Tempapan Kuala Village. The purposive sampling included religious leaders, two members of the zakat collection committee, and eight recipients of zakat fitrah outside the mustahiq at the Al-Manar Mosque in Tempapan Kuala Village. The results indicate that the distribution of zakat fitrah by amil to parties outside the mustahiq is driven by factors such as appreciation and gratitude, annual customs, amil's lack of understanding of zakat law, and inaccurate data collection of mustahiq. The consequences of this practice are that zakat becomes invalid according to sharia, is not well-targeted, and reduces social justice. Therefore, it is necessary to socialize zakat law, accurately record mustahiq, and establish a professional zakat collection committee so that zakat can be managed properly in accordance with Islamic law. Keywords: Distribution, Zakat, Fitrah, Amil, Mustahiq Abstrak Zakat merupakan ibadah yang disyariatkan dalam Islam dan wajib ditunaikan oleh setiap muslim yang mampu. Zakat memiliki fungsi yang sangat penting yaitu membantu orang yang membutuhkan dan mewujudkan keadilan sosial dalam masyarakat. Salah satu jenis zakat yaitu zakat fitrah yang wajib dibayarkan setiap bulan Ramadhan dan harus disalurkan kepada delapan golongan mustahiq sebagaimana diatur dalam Al-Qur"™an surat At-Taubah ayat 60 dan Undang-Undang Nomor 23 Tahun 2011 tentang pengelolaan Zakat. Namun pada praktiknya, penyaluran zakat fitrah yang dilakukan oleh amil di masjid Al-Manar desa Tempapan Kuala belum sesuai dengan ketentuan tersebut, karena selain zakat fitrah disalurkan kepada fakir, miskin, amil, dan mualaf, zakat fitrah juga disalurkan kepada pihak-pihak seperti dukun kampung, dukun beranak, penggali kubur, guru ngaji, muazin, ma"™asyiral, khatib, dan imam mesjid. Adapun rumusan masalah dalam penelitian ini yaitu "Faktor apa yang menyebabkan penyaluran zakat fitrah oleh amil diluar mustahiq di Masjid Al-Manar Desa Tempapan Kuala?". Tujuan dari penelitian ini adalah untuk mengetahui faktor yang menyebabkan terjadinya penyaluran zakat fitrah diluar mustahiq, akibat hukumnya, serta upaya yang dapat dilakukan agar penyaluran zakat fitrah sesuai dengan ketentuan hukum Islam. Penelitian ini merupakan penelitian hukum yuridis empiris dengan pendekatan deskriptif kualitatif. Jenis data yang digunakan diperoleh melalui penelitian lapangan (Field Research) dan penelitian kepustakaan (Library Research). Adapun teknik pengumpulan data yang dilakukan penulis yaitu yang pertama adalah teknik komunikasi secara langsung (Interview) terhadap sumber data yaitu panitia zakat dan pemuka agama masjid Al-Manar Desa Tempapan Kuala. Kemudian yang kedua yaitu teknik komunikasi tidak langsung (Questioner) yaitu masyarakat penerima zakat fitrah diluar mustahiq di masjid Al-Manar Desa Tempapan Kuala. Populasi penelitian mencakup pemuka agama, panitia amil zakat, dan penerima zakat fitrah diluar mustahiq dimasjid Al-Manar Desa Tempapan Kuala, sedangkan sampel diambil secara purposive meliputi pemuka agama, dua orang panitia amil zakat fitrah dan delapan orang penerima zakat fitrah diluar mustahiq di masjid Al-Manar Desa Tempapan Kuala. Hasil penelitian menunjukkan bahwa penyaluran zakat fitrah oleh amil kepada pihak diluar mustahiq disebabkan oleh faktor penghargaan dan ucapan terima kasih, kebiasaan tahunan, kurangnya pemahaman amil terhadap hukum zakat, serta pendataan mustahiq yang kurang tepat. Akibat praktik ini yaitu zakat menjadi tidak sah secara syariat, belum tepat sasaran dan berkurangnya keadilan sosial. Oleh karena itu, diperlukan sosialisasi hukum zakat, pendataan mustahiq secara tepat dan pembentukan panitia amil zakat yang profesional agar zakat dapat dikelola secara benar sesuai dengan syariat Islam. Kata Kunci: Penyaluran, Zakat, Fitrah, Amil, Mustahiq